2022
DOI: 10.1007/s10570-022-04565-y
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring the properties of nanocellulose-sepiolite hybrid nanopapers by varying the nanocellulose type and clay content

Abstract: The development of nanocellulose-clay materials resulted of great relevance, as it opened up the applications of nanocellulose, but it still requires new approaches that could contribute to improve the preparation procedures and the features of this type of biohybrid materials. In this context, nanocellulose-sepiolite (NC-S) biocomposite foams and films have already been successfully tested for some applications. However, the influence of the nanocellulose properties on sepiolite-cellulose interactions, and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 83 publications
1
6
0
Order By: Relevance
“…However, the ultrasonication of sepiolite suspension, beyond an additional trend to a slight improvement in the tensile strength, allowed to keep the transparency of the film containing 20% of sepiolite with a value close to that of the neat TEMPO CNF film. The mechanical properties of the composite films obtained in the present work are in line to those of related films reported in the literature (González del Campo et al, 2018;Martín-Sampedro et al, 2022). For example, Martín-Sampedro et al reported the preparation of hybrid nanopapers of TEMPO-oxidised CNF and sepiolite (20%) with a tensile strength of 79.0 MPa and Young's modulus of 4.7 GPa; our composite films presented comparable values for these properties (74.8 MPa and…”
Section: Effect Of Dispersion State Of Sepiolite On the Cnf-based Com...supporting
confidence: 91%
See 2 more Smart Citations
“…However, the ultrasonication of sepiolite suspension, beyond an additional trend to a slight improvement in the tensile strength, allowed to keep the transparency of the film containing 20% of sepiolite with a value close to that of the neat TEMPO CNF film. The mechanical properties of the composite films obtained in the present work are in line to those of related films reported in the literature (González del Campo et al, 2018;Martín-Sampedro et al, 2022). For example, Martín-Sampedro et al reported the preparation of hybrid nanopapers of TEMPO-oxidised CNF and sepiolite (20%) with a tensile strength of 79.0 MPa and Young's modulus of 4.7 GPa; our composite films presented comparable values for these properties (74.8 MPa and…”
Section: Effect Of Dispersion State Of Sepiolite On the Cnf-based Com...supporting
confidence: 91%
“…S3) showed a remarkable decrease of the intensity of all the bands in the mentioned region and, in particular, the very weak band due to the OH stretching in Si-O-H bonds at 3717 cm − 1 disappeared. The latter observation is an indication of the existence of interactions by hydrogen bonding between the silanol groups of the mineral surface and the hydroxyl groups of the CMC (Martín-Sampedro et al, 2022). Breaking of Mg-O bonds in the octahedral layer on the surface of the sepiolite crystals may also have occurred.…”
Section: Effect Of Additives On the Dispersion State And Structure Of...mentioning
confidence: 94%
See 1 more Smart Citation
“…The ancillary minerals exhibit a strong effect on the rheology of the suspension, relating to their individual morphology and lower particle density compared with GCC, hence exhibiting high volume concentration per unit weight in the formulation, especially under shear [ 7 , 26 ]. In considering the properties defined above ((i)–(iv)) we studied the stress-related viscoelastic and dilatant structure behavior of the complex material suspension.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the rheological behavior of suspension coatings that contain such minerals affects the end-point coating structure, including pore morphology, uniformity, and porosity, which, in turn, influence the surface sorption properties. Furthermore, due to the high surface area and/or aspect ratio of such ancillary minerals in the coating color matrix, once dried, and depending on orientation, they exhibit extensive volume fraction occupancy in the coating, and this feature can aid coverage of rough substrate surfaces [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%